Socioeconomic and Political Interplay Toward a Sustainable and Unified Sama Community - Borja-Dekit, Ludivina (PT. Riset Press International, 2025)
This article discusses the socioeconomic and political interplay in the Sama community in Mindanao. Through a comprehensive understanding of their historical background, this article aims to present policies for sustainable development of the long-aspired unified Sama community. A semi-systematic of secondary sources and major works about the Sama was conducted to reveal and outline the importance of identity, access to basic social services, and political representation and participation in ensuring sustainability. An integrative approach to the discussions highlighted from the International Bangsa Summity was also analyzed patterned from the analyses drawn after the systematic review. Interestingly, the analyses from both the semi-systematic and integrative reviews coincided. The article recommends that policies must be developed to support the Sama community through enhanced access to basic social services to develop and enkindle a sense of community, forging a sustainable sense of unity.